2004
DOI: 10.1085/jgp.200308990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of pH and Ca2+ Regulation of Aquaporin Water Permeability

Abstract: Aquaporins facilitate the diffusion of water across cell membranes. We previously showed that acid pH or low Ca2+ increase the water permeability of bovine AQP0 expressed in Xenopus oocytes. We now show that external histidines in loops A and C mediate the pH dependence. Furthermore, the position of histidines in different members of the aquaporin family can “tune” the pH sensitivity toward alkaline or acid pH ranges. In bovine AQP0, replacement of His40 in loop A by Cys, while keeping His122 in loop C, shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 41 publications
7
172
1
2
Order By: Relevance
“…AQP0 water conductance is pH-dependent with a maximum at pH 6.5 and only about half the activity at pH 10.5 12 . These conductance characteristics are not changed by proteolytic cleavage of AQP0 24 .…”
Section: Water Molecules In the Aqp0 Porementioning
confidence: 99%
See 1 more Smart Citation
“…AQP0 water conductance is pH-dependent with a maximum at pH 6.5 and only about half the activity at pH 10.5 12 . These conductance characteristics are not changed by proteolytic cleavage of AQP0 24 .…”
Section: Water Molecules In the Aqp0 Porementioning
confidence: 99%
“…The structure showed that AQP0 junctions are stabilised by specific interactions between tetramers in adjoining membranes involving almost exclusively proline residues. Calculated pore profiles also showed that the pore in junctional AQP0 is highly constricted due to a substantially extended ar/R constriction site and a novel second constriction site 7 , which may be involved in the pH regulation of AQP0 water conductance 12 .…”
mentioning
confidence: 90%
“…they are not constitutively locked into a rigid open state. For instance, the lens water channel AQP0 as well as plant aquaporins show changes in water permeability as a function of pH (37,38 (39,40) and the closely related AQP4 (41). Aquaporins are highly conserved in animals and plants.…”
Section: Pharmacological Agonists Of the Aquaporinsmentioning
confidence: 99%
“…Alterations in pH and calcium concentration, through interaction with specific histidine residues within the AQP pore have also been shown to cause different effects on water permeability in bovine and fish AQPs, despite sharing approximately 70% of their sequence (Nemeth-Cahalan et al, 2004). Regulation via gating mechanisms, which allow conformationally distinct open and closed states, has specifically been reported for plant and microbial AQPs (Tornroth-Horsefield et al, 2006).…”
Section: What Regulates Aqp Function?mentioning
confidence: 99%